Comparison of cerebrospinal fluid lactate with physical, cytological, and other biochemical characteristics as prognostic factors in acute bacterial meningitis - Sérgio Monteiro De Almeida; Nagyla C. Barros; Ricardo Petterle; Keite Nogueira (Arquivos de Neuro-Psiquiatria)
ABSTRACT Bacterial meningitis (BM) is associated with a high morbidity and mortality. Cerebrospinal fluid (CSF) lactate may be used as a prognostic marker of this condition. We hypothesized that CSF lactate levels would remain elevated in participants who died of acute BM compared with those who recovered from this disease. Objective: To evaluate the potential use of lactate and other CSF biomarkers as prognostic markers of acute BM outcome. Methods: This retrospective, longitudinal study evaluated dynamic CSF biomarkers in 223 CSF samples from 49 patients who fulfilled the inclusion criteria of acute BM, with bacteria identified by CSF culturing. The participants were grouped according to outcome: death (n = 9; 18.37%) and survival (n = 40; 81.63%). All participants received appropriate antibiotic treatment. Results: In the logistic regression model, lactate concentration in the final CSF sample, xanthochromia, and CSF glucose variation between the first and last CSF samples were predictors of a poor outcome (death). In contrast, decrease in CSF white blood cell count and CSF percentage of neutrophils, increase in the percentage of lymphocytes, and normalization of the CSF lactate concentration in the last CSF sample were predictors of a good prognosis. Conclusion: The study confirmed the initial hypothesis. The longitudinal analysis of CSF lactate is an important predictor of prognosis in acute BM.